Performance analysis of cost function based energy-efficient routing protocol in WSN - LIU Xing-cheng1; YUAN Dong-sheng1; LIANG Ping-yuan1; ZHANG Xiao-yu1 (Tongxin xuebao)
In CEERP（cost-based energy-efficient routing protocol）,the routing which had superior performance in WSN（wireless sensor network） could be found through calculating and comparing the cost function values.The cost function,energy consumption and delay performances of the previously proposed protocol,CEERP,were analyzed.The lower-and upper-bound of communication rounds performed by the WSN system and the calculation formula of delay were derived.The performance of various similar protocols was compared and discussed under the premise of the performance evalua-tion criterion,i.e.,the product of energy consumption and delay.At the same time,the performance of CEERP was simu-lated further on condition that the sensor nodes were deployed sparsely and the channels were non-ideal respectively.The results show that the comprehensive performance in terms of the product of energy consumption and delay of the CEERP outperforms that of other similar protocols.